VALIDAÇÃO DE PRODUTOS POR SATÉLITE ATRAVÉS DE MEDIÇÕES DO SITU PARA MONITORAR COBERTURAS TERRESTRE NO SUL DE PAMPAS (ARGENTINA) - Ferrelli, Federico; Soledad Brendel, Andrea; Miguel Eduardo Perillo, Gerardo; Cintia Piccolo, María (Caminhos de Geografia, 2020)
The study of regional-scale land covers is an expensive activity that requires specific equipment. This work aimed to analyze the precision and the accuracy between satellite products and a land cover map obtained using in situ measurements in the Sauce Grande river basin (Argentina). In order to do so, we carried out five field trips during 2018 to identify land covers. It was studied the reflectance of each class from georeferenced samples acquired with a spectrometer and a GPS. Besides, spectral indices of vegetation, water, and soil were calculated to analyze the spectral behavior of each class. With this information, we delimited regions of interest to perform the supervised method. Subsequently, we downloaded the MODIS and ESA Landcover products. Then, we established a pixel of 300 meters for the three maps with matrix metrics. The Kappa coefficient, the overall accuracy, as well as the user and producer ones, were calculated to evaluate the estimated land cover against the measured ones. Results showed that MODIS-Landcover presents excellent agreements for determining crops and grasslands, while ESA-Landcover for urban expansion and water bodies.